Viability of Parhyale hawaiensis for chronic ecotoxity testing: the case study of diflubenzuron - Assano, Patricia; Umbuzeiro, Gisela; Diehl, Otávio; Santos, Amanda dos; Vacchi, Francine; Oliveira, Rhaul de (Revista dos Trabalhos de Iniciação Científica da UNICAMP, 2019)
Parhyale hawaiensis is an marine amphipod and attractive model organism for ecotoxicology. The insect growth regulator diflubenzuron (DFB) is a chitin syntheis inhibitor insecticide with have pronounced toxic effects on non-target organisms, especially insects and crustaceans. This study aimed to evaluate the toxicity assessment of diflubenzuron using a miniaturized approach for chronic test with Parhyale hawaiensis, previousily standarized in our reasearch group.